Serum and Urinary Neutrophil Gelatinase-Associated Lipocalin Are Not Associated With Serum Redox Parameters in Amateur Athletes After an Ultramarathon - Loureiro, Adriano César Carneiro; Nocrato, Gabriella Fontenele; Correia, André Luis Lima; de Matos, Robson Salviano; Filho, Júlio César Chaves Nunes; Daher, Elisabeth De Francesco; Pinto, Flávio Henrique Macedo; de Oliveira, Ariclécio Cunha; Ceccatto, Vania Marilande; Fortunato, Rodrigo Soares; de Carvalho, Denise Pires (Frontiers in Physiology, 2022)
Objective To evaluate the relationship between oxidative stress and NGAL levels in blood and urine of amateur athletes after participating in a 100 km ultramarathon. Methodology The sample was composed of seven athletes, submitted to anthropometric assessment, cardiopulmonary exercise test, collection of urine and blood, measurement of body weight. The rate of perceived exertion (RPE), competition duration, heart rate (HR), energy expenditure and oxygen consumption (V’O2”) were also measured during the event. The energy consumption during the race was verified at its end. The analyses were based on the means (M) and respective standard deviations (SD), with statistical significance set at 5% (p < 0.05). Paired t-test was used for comparison between the periods before and after the competition, and Pearson’s correlation coefficient was used to measure the linear correlation between quantitative variables. Results Body mass index (BMI) of the sample was 25.75 kg/m2 ± 3.20, body fat percentage 18.54% ± 4.35% and V’O2”max 48.87% ± 4.78. Glucose, cortisol, and neutrophil gelatinase-associated lipocalin (NGAL) (p < 0.01) as well as glutathione peroxidase (GPx) active were higher after the race when compared to basal values. Moreover, lactate, creatinine, microalbuminuria, and glomerular filtration rate (GFR) (p < 0.001) were also higher after the race. After the competition, there was a significant correlation only between serum NGAL and creatinine, which was classified as strong and positive (r: 0.77; p < 0.05). There was a significant reduction (p < 0.05) of body weight after the event (72.40 kg ± 9.78) compared to before it (73.98 kg ± 10.25). In addition, we found an increase of RPE (p < 0.001) after the race. The competition lasted 820.60 min (±117.00), with a 127.85 bpm (±12.02) HR, a 2209.72 kcal ± 951.97 energy consumption, 7837.16 kcal ± 195.71 energy expenditure, and 28.78 ml/kg/min–1 (±4.66) relative V’O2”max. Conclusion The lack of correlation between oxidative stress biomarkers and serum and urine NGAL suggests that NGAL is more sensitive to inflammatory processes than to ROS levels.